2014
DOI: 10.1371/journal.pone.0109632
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in Patients with Psoriasis: A Population-Based Cohort Study

Abstract: PurposePsoriasis is a chronic inflammatory disease characterized by a systemic immunological response which is mainly driven by activated T helper (Th) 1 and Th17 lymphocytes. Like psoriasis, sarcoidosis is a chronic inflammatory disorder with Th1/Th17-driven inflammation. Therefore, we investigated the risk of sarcoidosis in patients with psoriasis compared to the background population in a nationwide cohort.MethodsThe study included the entire Danish population aged ≥10 years followed from 1st January 1997 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…Our analysis showed that sarcoidosis patients could have been likely to develop SLE (aOR, 2.98), but the small case number rendered the statistical evaluation insignificant. The association between sarcoidosis and psoriasis was demonstrated in a large Denmark cohort study; however, there were only a few Asian people, two Japanese cases, reported in the English‐language published work to show coexistence of both diseases . The discrepancy in the comorbidity profiles of sarcoidosis patients may, at least partially, result from different genetic backgrounds and environmental factors that await additional studies to clarify the aforesaid association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis showed that sarcoidosis patients could have been likely to develop SLE (aOR, 2.98), but the small case number rendered the statistical evaluation insignificant. The association between sarcoidosis and psoriasis was demonstrated in a large Denmark cohort study; however, there were only a few Asian people, two Japanese cases, reported in the English‐language published work to show coexistence of both diseases . The discrepancy in the comorbidity profiles of sarcoidosis patients may, at least partially, result from different genetic backgrounds and environmental factors that await additional studies to clarify the aforesaid association.…”
Section: Discussionmentioning
confidence: 99%
“…The association of sarcoidosis with several other autoimmune comorbid diseases as frequently reported before was not demonstrated in our analysis, such as celiac disease, autoimmune hepatitis, inflammatory bowel disease, MS, systemic sclerosis, SLE and psoriasis. 5,9,11,[15][16][17][18][20][21][22][23]35 There were marked racial differences in the prevalence of the first five diseases as mentioned above with the Westerners being more predisposed to those autoimmune comorbidities than the Asian people. [36][37][38][39][40] Hence, the different comorbidity profiles disclosed in our analysis may be attributed to the low prevalence of those diseases in the Taiwanese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of sarcoidosis and psoriasis also has been reported in both case series and population-based cohorts, which is hypothesized to occur as a result of overlapping pathogenetic mechanisms. [58][59][60] Lichenoid sarcoidosis can present as small, flattopped, skin-colored to erythematous papules; however, it can be differentiated from lichen planus by a lack of overlying white lacy marks (Wickham striae). This cutaneous presentation has been reported most often in children, can be localized or extensive, and can be eruptive in nature.…”
Section: Less Common Morphologiesmentioning
confidence: 99%
“…Existen pocos casos documentados de asociación psoriasissarcoidosis 2-4 , aunque recientemente se ha observado un mayor riesgo de padecer sarcoidosis en pacientes diagnosticados de psoriasis respecto a la población general, siendo además esta asociación severidad-dependiente 5 .…”
unclassified